Oviposition Substrate of the Mountain Fly Drosophila nigrosparsa (Diptera: Drosophilidae) - Kinzner, Martin-Carl; Tratter, Magdalena; Bächli, Gerhard; Kirchmair, Martin; Kaufmann, Rüdiger; Arthofer, Wolfgang; Schlick-Steiner, Birgit C.; Steiner, Florian M. (PLOS ONE, 2016)
The survival of insect larvae often depends on the mother’s choice of oviposition substrate, and thus, this choice is an essential part of an insect species’ ecology. Especially species with narrow substrate preferences may suffer from changes in substrate availability triggered by, for example, climate change. Recent climate warming is affecting species directly (e.g., physiology) but also indirectly (e.g., biological interactions) leading to mismatching phenologies and distributions. However, the preferred oviposition substrate is still unknown for many drosophilid species, especially for those at higher elevations. In this study, we investigated the oviposition-substrate preference of the montane-alpine fly Drosophila nigrosparsa in rearing and multiple-choice experiments using natural substrates in the laboratory. Insect emergence from field-collected substrates was tested. More than 650 insects were reared from natural substrates, among them 152 drosophilids but no individual of D. nigrosparsa. In the multiple-choice experiments, D. nigrosparsa preferred ovipositing on mushrooms (> 93% of eggs); additionally, a few eggs were laid on berries but none on other substrates such as cow faeces, rotten plant material, and soil. The flies laid 24 times more eggs per day when mushrooms were included in the substrates than when they were excluded. We infer that D. nigrosparsa is a mushroom breeder with some variation in oviposition choice. The flies favoured some mushrooms over others, but they were not specialised on a single fungal taxon. Although it is unclear if and how climate change will affect D. nigrosparsa, our results indicate that this species will not be threatened by oviposition-substrate limitations in the near future because of the broad altitudinal distribution of the mushrooms considered here, even if the flies will have to shift upwards to withstand increasing temperatures.